Assessment of Clinical Efficacy of Microbiome and Topical Hyaluronic Acid Gel Combination Therapy in Minor Aphthous Ulcer Management – A comparative study - Shilpa Shree Kuduva Ramesh; Jayachandran Sadaksharam (Journal of Indian Academy of Oral Medicine and Radiology, 2021)
Aim: This study aimed to determine the clinical efficacy of the combination of microbiomes and 0.2% topical hyaluronic acid gel, alongside topical monotherapy with 0.2% hyaluronic acid gel and steroids, respectively, in minor aphthous ulcer management. Subjects and Methods: A total of 45 patients were divided into three groups: Group A (n = 15) –– a combination of microbiome therapy––pre- and probiotics capsules p. o. and topical 0.2% hyaluronic acid gel; Group B (n = 15)––topical 0.2% hyaluronic acid gel; and Group C (n = 15)––0.1% triamcinolone acetonide oromucosal paste. Numerical rating scale (NRS) for pain, ulcer dimensions measured by Digital Planimetry using android mobile application to determine the degree of ulcer healing (%) and occurrence of new ulcers were recorded on 0, third, and seventh days of treatment. Statistical Analysis Used: One-way ANOVA with post hoc Tukey test among the groups and independent t - test for the degree of ulcer healing between third and seventh days were applied. Results: NRS for pain at day 3 showed a statistically significant pain reduction in Group A compared with Groups B and C (P = 0.04, 0.01, respectively). Though Group A showed the highest grade of closure (93.4 ± 2.5%) and a greater decrease in mean NRS score (0.2 ± 0.42) on the seventh day when compared to Groups B and C, results were not statistically significant (P > 0.05). Conclusion: Microbiome and topical hyaluronic acid gel combination therapy helps in immediate pain relief and faster healing. Hence, it could be an excellent alternative for topical steroid management.